Effectiveness of digital gaming intervention in enhancing adolescents’ knowledge and attitudes toward sexual and reproductive health: a systematic review - Cahyani, Reztika; Rekawati, Etty; Mulyono, Sigit; Widyatuti (Universitas Gadjah Mada, 2025)
Purpose: Adolescents often lack adequate sexual knowledge, leading to risky behaviors. Traditional sexual health education is usually less effective in enhancing the motivation and engagement of students. Digital gaming interventions offer a promising alternative in the digital era, providing interactive, engaging, and safe learning experiences. This systematic review aims to analyze the effectiveness of digital games in enhancing adolescents’ knowledge and attitudes toward sexual and reproductive health education. Methods: This systematic review followed the PRISMA guidelines and employed the Joanna Briggs Institute (JBI) critical appraisal. A literature search across ClinicalKey, Cochrane, EBSCO, ScienceDirect, and Scopus identified studies published between 2015 and 2025. The inclusion criteria were original, quantitative studies in English that were freely accessible and focused on digital gaming interventions in adolescent reproductive health. Conventional games or unrelated topics were excluded. Four authors independently screened and reviewed the studies, yielding nine articles for analysis. Results: Nine studies with 6,969 adolescents (aged 11–24) from six countries were included. Digital game interventions significantly improved SRH knowledge and attitudes, with effects ranging from modest (6.27% gain; β = 0.05–0.08) to numerous (η² = 0.80). The small number of studies, design heterogeneity, and cultural differences limit the evidence. Conclusion: Digital gaming intervention improves adolescents’ SRH knowledge and attitudes across contraception, STI prevention, and healthy relationships. However, the limited number of studies, design heterogeneity, and cultural variations restrict generalizability. Future rigorous studies and integration into schools and community programs are recommended. Registered in PROSPERO, ID CRD4202511 68048.